Interdisciplinary pathways for advancing social justice, peace, and sustainable development in social work education and professional practice - Engelbrecht, Lambert K.; Ncube, Mpumelelo E. (Social Work/Maatskaplike Werk, 2025)
This issue of Social Work/Maatskaplike Werk celebrates the twenty-fifth anniversary of the Association of South African Social Work Education Institutions (ASASWEI) and the journal’s diamond jubilee, highlighting interdisciplinary scholarship that advances social justice, peace, and sustainable development in social work education and practice. It includes a special article, ten research studies, a book review, and a note from practice. Together, these contributions demonstrate how research, education, and practice intersect to strengthen professional capacity, inform policy, and foster transformative interventions for individuals, families, and communities.